2020
DOI: 10.21203/rs.3.rs-124734/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initiation of Hepatitis C treatment in two rural Rwandan districts: A mobile clinic approach

Abstract: Background: To eliminate hepatitis C, Rwanda is conducting national mass screenings and providing hepatitis C patients with free access to Direct Acting Antivirals (DAAs). Until 2020, all prescribers trained and authorized to initiate DAA treatment were based at District Hospitals, and access to DAAs remains expensive and geographically difficult for rural patients. We designed and implemented a mobile hepatitis clinic to provide DAA treatment initiation at primary-level health facilities among hepatitis C pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Because increased age is a strong risk factor for hepatitis C in Rwanda, our study population was largely composed of older individuals who would have been most affected by this educational disparity. We believe that the predominance of women in our study primarily reflects a structural gender imbalance in the Rwandan population, which is pronounced in older age groups [27], because previous research in this setting has demonstrated similar linkage to care rates among men and women [21]. Even after treatment initiation, several common misconceptions about hepatitis C persisted.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Because increased age is a strong risk factor for hepatitis C in Rwanda, our study population was largely composed of older individuals who would have been most affected by this educational disparity. We believe that the predominance of women in our study primarily reflects a structural gender imbalance in the Rwandan population, which is pronounced in older age groups [27], because previous research in this setting has demonstrated similar linkage to care rates among men and women [21]. Even after treatment initiation, several common misconceptions about hepatitis C persisted.…”
Section: Discussionmentioning
confidence: 81%
“…However, this inverse association could also reflect that quality of care was rated very highly overall and we may not have observed enough variation in satisfaction to observe the expected association. Because the novel mobile clinic approach used by our team is associated with substantial time and cost savings for patients [21], high self-reported satisfaction could also primarily reflect high patient satisfaction with the overall approach used by our team rather than specifically reflecting patient-provider communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although viral load testing was a barrier to provision of care, our treatment initiation and treatment assessment rates were quite high. These outcomes were achieved in the context of a mobile clinical campaign, which has previously been reported as a low-cost strategy to support linkage to care, and may be a scalable model for improving patients' access to care (13).…”
Section: Discussionmentioning
confidence: 94%
“…To facilitate patients' access to care during the period of the screening and linkage to care activities described in this study, PIH/IMB organized a mobile clinic where clinicians and lab technicians from district hospitals met with patients at their nearest health facilities. This approach allowed patients to attend their local primary-level health centres for same-day clinical consultations, lab exams and treatment initiation, as has been described in detail elsewhere (13).…”
Section: Study Settingmentioning
confidence: 99%